Motivasi Konsumen dalam Pembelian Tiket Konser NCT: Studi pada Penggemar K-Pop di Indonesia - Putri, Novaldha Andianthie; Setiawan, Joe Harrianto (Universitas Mataram, 2025)
The phenomenon of music concerts, particularly K-Pop concerts, has experienced a significant increase in Indonesia. Fan decisions regarding the purchase of concert tickets are driven by a variery of motivations. This study aims to analyze the factors influencing NCTzen’s decision to attend NCT concerts, utilizing consumer motivation theory and Maslow’s hierarchy of needs. A qualitative research method was employed, involving in depth interviews with four concert attendees. Data analysis was conducted using the data analysis framework developed by Miles & Huberman. The findings indicate that concert ticket purchase decisions are influenced by both rational and emotional motivations, with emotional factors being predominant. The study concludes that concerts serve not merely as entertainment, but also as an integral part of fans’ lifestyle and social identity.